Методика написання наукової статті здобувачами вищої освіти технічних спеціальностей в умовах військового стану - Самойчук, Кирило Олегович; Samoichuk, Kyryl (Запоріжжя : 2023, 2023)
UA: Важливим компонентом освітніх програм підготовки бакалаврів та магістрів технічних спеціальностей є вміння на навички написання наукових робіт. В статті викладена методика написання наукових статей (тез доповідей), курсових і дипломних робіт для здобувачів вищої освіти технічних спеціальностей в умовах негативного впливу військових дії на території України, які знижують мотивацію та створюють відоме відчуття виснаженості та відсутності сил. Надані способи боротьби з цим явищем, основним з яких є метод поступового входження в роботу. Наданий план, способи та прийому роботи над статтею й практичні рекомендації для швидкого та якісного створення нових науково-методичних робіт студентами. EN: An important component of educational programs for bachelors and masters in technical specialties is the ability to write scientific papers. The article describes the method of writing scientific articles (theses of reports), course and diploma theses for students of higher education in technical specialties under the conditions of the negative impact of military operations on the territory of Ukraine, which reduce motivation and create a well-known feeling of exhaustion and lack of strength. Methods of combating this phenomenon are provided, the main of which is the method of gradual entry into work. The plan, methods and reception of work on the article and practical recommendations for the quick and high-quality creation of new scientific and methodical works by students are provided.
The methodology of writing a scientific article by higher education acquires of technical specialties under the conditions of the military state
Keywords: написання наукових робіт; методика написання наукової статі; студенти; здобувачі вищої освіти; виснаженість внаслідок військового стану; writing scientific papers; the method of writing a scientific article; students, students of higher education; exhaustion due to martial law